Factors associated with survival probability in autopsy-proven frontotemporal lobar degeneration. Issue 2 (5th July 2007) - Xie, S X; Forman, M S; Farmer, J; Moore, P; Wang, Y; Wang, X; Clark, C M; Coslett, H B; Chatterjee, A; Arnold, S E; Rosen, H; Karlawish, J H T; et al.
Abstract : Objective: To examine the clinical and pathological factors associated with survival in autopsy-confirmed frontotemporal lobar degeneration (FTLD). Methods: The final analysis cohort included 71 patients with pathologically proven FTLD, excluding patients with clinical motor neuron disease (MND), evaluated at the University of Pennsylvania or at the University of California, San Francisco. We assessed clinical and demographic features; cognitive functioning at presentation; genetic markers of disease; and graded anatomical distribution of tau, ubiquitin and amyloid pathology. Results: The tau-negative group (n = 35) had a median survival time of 96 months (95% CI: 72–114 months), whereas the tau-positive group (n = 36) had a median survival time of 72 months (95% CI: 60–84 months). Patients with tau-positive pathology across all brain regions had shorter survival than those with tau-negative pathology in univariate Cox regression analyses (Hazard ratio of dying = 2.003, 95% CI = 1.209–3.318, p = 0.007). Conclusions: Tau-positive pathology represents a significant risk to survival in FTLD, whereas tau-negative pathology is associated with a longer survival time when clinical MND is excluded.